ChemInform Abstract: Controlled Synthesis of Carbon‐Supported Gold Clusters for Rational Catalyst Design. Issue 49 (17th November 2016) - Yamazoe, Seiji; Yoskamtorn, Tatchamapan; Takano, Shinjiro; Yadnum, Sudarat; Limtrakul, Jumras; Tsukuda, Tatsuya
Abstract: Review: [40 refs.